pH-Responsive fluorescent supramolecular nanoparticles based on tetraphenylethylene-labelled chitosan and a six-fold carboxylated tribenzotriquinacene - Nan Yang; Yi-Yan Zhu; Wei-Xiu Lin; Yi-Long Lu; Wen-Rong Xu (Beilstein Journal of Organic Chemistry, 2023)
We synthesized a new tetraphenylethylene-modified chitosan bioconjugate, CS-TPE, that shows the aggregation-induced emission effect. It can self-assemble into fluorescent polymeric nanoparticles in an aqueous solution at pH 5.3 either alone or with the water-soluble bowl-shaped six-fold carboxylated tribenzotriquinacene derivative TBTQ-C6 via host–guest binding. The spherical nanoparticles formed by CS-TPE amphiphiles or TBTQ-C6/CS-TPE supra-amphiphiles disintegrated under alkaline stimulation at pH 10.4 and the dispersion of the aggregates after the collapse in the presence of TBTQ-C6 was greatly improved. In addition, the fluorescence of CS-TPE was significantly enhanced by introducing TBTQ-C6, and remained relatively stable with variations in pH for both CS-TPE and TBTQ-C6/CS-TPE. Such pH-responsive supramolecular spherical nanoparticles with stable fluorescence emission based on CS-TPE or TBTQ-C6/CS-TPE may find applications in various fields, including the development of visual oral drug delivery systems.